High yielding varieties for enhancing the production of small millets in India - Hariprasanna, K (Indian Farming, 2023)
Small millets are a group of small-grained cereal crops, have a unique place in Indian agriculture though they contribute less than 1% to the annual cereal grain production. Traditionally these crops have been the indispensable component of dry farming system and areas where other crops can not be cultivated profitably. These crops are important in tribal and hill agriculture.